Investigating suspected immune deficiency in children. Issue 6 (June 2022) - Torpiano, Paul; Buckland, Matthew; Gilmour, Kimberly
Abstract: The International Union of Immunological Societies now recognizes over 430 single gene inborn errors of immunity, making the investigation of suspected immunodeficiency in children increasingly complex. The use of immunomodulatory therapies, including biologics, may also cause both transient and permanent secondary immunodeficiency. This review outlines a practical approach to guide paediatric doctors and allied health professionals investigating children with suspected immune deficiency, starting with a detailed clinical assessment of history and examination, as well as baseline investigations to exclude secondary immunodeficiency and screen for organ-specific complications for immunodeficiency. This should be followed as appropriate by a basic assessment of humoral, cell-mediated, phagocytic, and innate immunity, the results of which would instruct the necessity of confirmatory testing using functional and protein expression assays, as well as genetic testing. The authors also recommend an approach for screening for immunodeficiency in asymptomatic neonates, children with a strong family history of primary immunodeficiency, or those diagnosed with genetic syndromes associated with immunodeficiency.